2014
DOI: 10.1053/j.ajkd.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Urine Stability Studies for Novel Biomarkers of Acute Kidney Injury

Abstract: BACKGROUND The study of novel urinary biomarkers of acute kidney injury has expanded exponentially. Effective interpretation of data and meaningful comparisons between studies require awareness of factors that can adversely affect measurement. We examined how variations in short-term storage and processing might affect measurement of urine biomarkers. STUDY DESIGN Cross-sectional, prospective. SETTING & PARTICIPANTS Hospitalized patients from two sites: Yale New Haven Hospital (n= 52) and University of Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 23 publications
1
47
0
Order By: Relevance
“…Second, biomarker levels could potentially be affected by storage of biological specimens. Though NGAL and IL-18 levels do not seem to be greatly affected by short-term handling variations, 52 levels may decline over time in frozen samples. In one study, NAG was shown to decline 28-fold over one year while stored at −80°C, 53 although this finding has not been confirmed.…”
Section: Discussionmentioning
confidence: 92%
“…Second, biomarker levels could potentially be affected by storage of biological specimens. Though NGAL and IL-18 levels do not seem to be greatly affected by short-term handling variations, 52 levels may decline over time in frozen samples. In one study, NAG was shown to decline 28-fold over one year while stored at −80°C, 53 although this finding has not been confirmed.…”
Section: Discussionmentioning
confidence: 92%
“…33 It has recently been shown that post-centrifugation delays of up to 48 hours at either RT or 4°C do not have a significant impact on the levels of biomarkers of acute kidney injury (neutrophil gelatinase-associated lipocalin, interleukin-18, kidney injury molecule 1, liver-type fatty acid-binding protein). 34 In order to prevent degradation of more sensitive molecules, a post-centrifugation delay of less than 2 hours at 4°C, storage of urine supernatant at -80°C, and avoiding freeze/thaw cycles is recommended.…”
Section: Urine Processing Methods 355 Discussionmentioning
confidence: 99%
“…All urine samples will be kept in frozen form for 5 years at −80°C, establishing a ‘biorepository’ of urinary samples. Stability of urine for processing and analysis of urinary biomarkers after storage in this manner has been validated [21]. …”
Section: Methodsmentioning
confidence: 99%